Effects of tillage, moisture and fertilization on the yield of the common bean and the pathogenicity of Macrophomina phaseolina (Tassi) Goid - Lira-Méndez, Krystal; Salinas-García, Jaime Roel; Díaz-Franco, Arturo; Mayek-Pérez, Netzahualcóyotl (Revista Mexicana de Ciencias Agrícolas, 2018)
The fungus Macrophomina phaseolina (Tassi) Goid causes the ‘charcoal rot’ disease in common beans (Phaseolus vulgaris L.) and other crops and reduces plant growth and grain yield. In this work we determined the effects of four tillage levels (moldboard plow, shred-bedding, subsoil-bedding, no or zero tillage); two levels of soil moisture (rainfed, irrigated) and two of fertilization (chemical, using the formula 40-20-00 NPK; biological, using the mycorrhiza Glomus intraradices) in grain yield of the variety Negro INIFAP during 2006 and 2007 in Río Bravo, Mexico as well as the pathogenicity of M. phaseolina. Experiments were established in a subdivided plot treatment arrangement with three replications. One isolate of M. phaseolina was obtained from plants collected in each experimental unit and the pathogenicity was determined in seeds of five common bean cultivars (Azufrado Tapatío, Bayo Madero, Flor de Mayo Bajío, Negro Altiplano, and Negro INIFAP). Irrigation and G. intraradices increased grain yield by 144% and 12%, in comparison to with rainfed conditions and chemical fertilization, respectively. The M. phaseolina isolates from irrigated, chemically fertilized and with subsoil-bedding or moldboard plow tillage were more aggressive in bean seeds. The application of mycorrhiza and conservative tillage promote soil sustainability and they could be used as integrated management measures of M. phaseolina in common beans.
Keywords: Phaseolus vulgaris L.; crop management; charcoal rot; tillage systems